High body mass index in children with sickle cell disease: a retrospective single-centre audit. Issue 1 (23rd October 2018) - Hall, Rachael; Gardner, Kate; Rees, David C; Chakravorty, Subarna
Abstract : Objective: To assess the prevalence of high body mass index (BMI) in children with sickle cell disease and assess correlation between BMI and disease severity. Design: Retrospective chart review followed by statistical analysis. Setting: A single tertiary paediatric clinic in inner city London. Patients: All patients with sickle cell disease, including homozygous haemoglobin (HbSS) and compound heterozygous Hb (HbSC), age 2–18 years receiving clinical care at the centre, were included in the study. Interventions: Height and weight measurements, steady-state laboratory blood tests, hospital admission rates, adjunct therapy such as hydroxycarbamide or blood transfusions and obstructive sleep apnoea (OSA) data were obtained from the hospital electronic patient records. Main outcome measures: To study the prevalence of high BMI and to identify any correlation between BMI and disease severity. Results: 385 patients were included. 64 children (17%) were overweight or obese, of which a significantly higher number of children with HbSC were obese or overweight (23 out of 91, 25%) compared with those with HbSS (36 out of 273, 13%), p≤0.001. No correlation was found between high BMI and presence of OSA, and markers of disease severity such as admission rates, fetal haemoglobin or lactate dehydrogenase levels. Conclusions: High BMI did not correlate with disease severity in this cohort of patients with sickle cell disease. Obesity was more prevalent in females and those with HbSC. Further prospective studies are needed to determine long-term effects of BMI in disease severity and outcome.